(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2012)
The influence of economic depression during late 2000 is widely experienced across the world and has affected almost every sector to some extent. The objective of present paper is to analyze this impact on media industry. Hereby, the paper will study the different fields in the media industry; they are – advertising, news and entertainment. These fields will be studied in a way to understand the degree of influence of economic crisis that followed in fiscal year 2008. The research will seek to examine the efforts put by the industry to overcome the crisis. Therefore, the paper will look at the growth drivers or the various mechanisms that were adopted by the respective media channels.